1998
DOI: 10.1007/s003810050191
|View full text |Cite
|
Sign up to set email alerts
|

Reversible cerebral perfusion alterations in children with transient mutism after posterior fossa surgery

Abstract: Mutism is an infrequent and transitory complication observed following posterior fossa surgery. Patients become mute in the immediate postoperative period, with restoration of speech within a few weeks in the absence of additional neurological alterations. The anatomical structures thought to be involved are the connections between the cerebellar dentate nucleus, the ventrolateral nucleus of the contralateral thalamus and the supplementary motor area. In an attempt to understand the pathophysiology of this syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 22 publications
2
31
0
1
Order By: Relevance
“…We fully agree that the study of Miller et al 1 adds important evidence to current insights in the possible cause and pathophysiologic mechanism underlying the PFS, but we would like to point out that CCD has already been reported on several previous occasions as a possible explanation for transient postoperative mutism 2,3 and for the constellation of neurobehavioral and affective symptoms characterizing PFS in the pediatric population. [4][5][6] For instance, Mariën et al (2001Mariën et al ( , 2003 4,6 reported the preliminary results of a prospective study in which the pathophysiologic role of CCD in PFS was explored.…”
supporting
confidence: 65%
“…We fully agree that the study of Miller et al 1 adds important evidence to current insights in the possible cause and pathophysiologic mechanism underlying the PFS, but we would like to point out that CCD has already been reported on several previous occasions as a possible explanation for transient postoperative mutism 2,3 and for the constellation of neurobehavioral and affective symptoms characterizing PFS in the pediatric population. [4][5][6] For instance, Mariën et al (2001Mariën et al ( , 2003 4,6 reported the preliminary results of a prospective study in which the pathophysiologic role of CCD in PFS was explored.…”
supporting
confidence: 65%
“…63 Multiple studies have supported the theory of cerebellocerebral diaschisis using different imaging techniques that revealed decreased blood flow, metabolic action, and function within supratentorial structures that play a crucial role in speech production, such as the thalami, inferior frontal gyrus, and temporal lobe. 26,34,63,65,83 In almost every case the abnormal findings returned to normal when mutism resolved.…”
Section: Pathophysiologymentioning
confidence: 93%
“…Also in case studies of children with PFS after cerebellar tumor surgery, bilateral reduction of supratentorial cerebral perfusion was found [9,10,11]. Reduction of cerebral perfusion is believed to be induced by a usually transient perturbation of the dentato-thalamic-cortical pathways [8].…”
Section: Discussionmentioning
confidence: 99%
“…Characteristically the impairments recede after days to months. MRI does not explain the anatomical basis of neurologic deficits of PFS, but single photon emission computed tomography (SPECT) findings suggest a transient perturbation of the dentato-thalamo-cortical pathways, resulting in a diminished or altered function of supratentorial brain structures [8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%